Revealing contrasting genetic variation and study of genetic diversity in urdbean (Vigna mungo (L.) Hepper) using SDS-PAGE of seed storage proteins - Tripathy, Swapan Kumar; Mohanty, Priyadarshini; Jena, Monalisha; Dash, Gokul Bihari; Pradhan, Kedareswar; Nayak, Pramod Kumar; Dash, Sasmita; Lenka, Devraj; Mishra, Dayanidhi; Mohapatra, Pavitra Mohan; Swain, Digbijaya; Senapati, Niranjan (Research in Biotechnology, 2016)
Total seed storage protein profiles of 20 urdbean genotypes including the popular variety T9 were analysed by Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE). 14 genotypes could be clearly identified based on genotype-specific seed protein fingerprints while rest of the test genotypes were categorized into three protein types. Dendrogram based on electrophoretic data clustered the genotypes into seven groups at 78.5% phenon level.Â TU 95-1 with TU 12-25-4 revealed lowest similarity index value (0.33) followed by TU 95-1 with PU 30 and KU 96-3(SI=0.35). Clustering pattern revealed distinctly divergent group formed by TPU 95-1 and TPU 4. These may serve as a valuable source genotype in recombination breeding. Â Â Key words: Seed storage protein profiling, SDS-PAGE, Genetic variation, urdbean.